CORRECTION OF MICROCIRCULATORY DISORDERS IN NON-ALCOHOLIC FATTY LIVER DISEASE IN PATIENTS WITH CHRONIC HEART FAILURE PATIENTS - M. E. Statsenko; S. V. Turkinа; M. A. Kosivtsova (Архивъ внутренней медицины)
Combined liver damage in patients with chronic heart failure and non-alcoholic fatty liver disease leads to the formation of pathological hemodynamic types of microcirculation with prevalence of shunt blood flow, nutritional deficiency, that correlated with changes in the functional state of the liver. Using cytoprotector mexicor for 16 weeks as part of the basic treatment of patients with chronic heart failure and non-alcoholic fatty liver disease can correct these microcirculatory disorders, has a beneficial effect on endothelial function, autonomic tone of microvessels, which is accompanied by the positive dynamics of indicators of cytolysis and cholestasis.